2011
DOI: 10.1016/j.ijid.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and potential clinical value of the LightCycler SeptiFast assay in the management of bloodstream infections occurring in neutropenic and critically ill patients

Abstract: The SeptiFast assay is a valuable ancillary method for the diagnosis of bloodstream infections in neutropenic and ICU patients. In these clinical settings, results of the SeptiFast assay may lead to a more targeted antibiotic therapy early after the onset of fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 21 publications
2
20
1
1
Order By: Relevance
“…In our research in DNA-based detection systems, we found genetic material from P aeruginosa, A baumannii, and A fumigatus in patients with blood cultures that showed no growth. This finding does not seem to depend on the characteristics of the patients, as it has also been reported in other studies focused on immunosuppressed patients, 34,35 transplant recipients, 36 and patients with sepsis. 11,37 SeptiFast has some disadvantages, including false-negatives and problems derived from the technique itself.…”
Section: Discussionsupporting
confidence: 86%
“…In our research in DNA-based detection systems, we found genetic material from P aeruginosa, A baumannii, and A fumigatus in patients with blood cultures that showed no growth. This finding does not seem to depend on the characteristics of the patients, as it has also been reported in other studies focused on immunosuppressed patients, 34,35 transplant recipients, 36 and patients with sepsis. 11,37 SeptiFast has some disadvantages, including false-negatives and problems derived from the technique itself.…”
Section: Discussionsupporting
confidence: 86%
“…These results stand in contrast to the results of our study, where the blood cultures showed a higher pathogen detection rate. Other recent research is in line with our results: studies investigating patients with suspected sepsis in the emergency department [21], patients with malignancies and sepsis [22], critically ill neutropenia patients [23] and etiological diag- nosis of community-onset bloodstream infections [24]. The other two PCR assays (SepsiTest® and VYOO®) are less well studied in respect to sepsis.…”
Section: Discussionsupporting
confidence: 88%
“…Multiplex realtime PCR assays, on the other hand, facilitate the rapid identification of pathogens and are a promising approach for routine use. Several studies have shown the value of this diagnostic tool for rapid detection of bloodstream pathogens, particularly in pretreated patients (4,5,25). Also, for clinical specimens other than blood, these assays show a great potential for diagnosing bacterial infections (21).…”
mentioning
confidence: 99%